Customer Segmentation With K-Means Clustering Suzuki Mobil Bandung Customer Case Study - Dedi Kadarsah; Jerry Heikal (Jurnal Indonesia Sosial Teknologi, 2024)
In the city of Bandung, it is recorded that until February 2023 as many as 500 thousand private cars crowded the streets in the city of Bandung. People's needs for private cars are met through the purchase of new cars from dealers or used purchases. As a dealer, the main task is to meet car sales targets every month and year. Suzuki dealers, especially in Bandung, do not have solid information about what type of car is most liked by the people of Bandung, what is the background of the customers and what marketing efforts are most optimal to increase sales. Suzuki car sales data for the June-October 2023 period was analyzed as many as 165 sales from various types of cars, customer domicile, customer's proffesion and marketing efforts carried out until the purchase occurred and the choice of payment method. In this paper, a clustering analysis of the K-means method with 4 clusters with car type, customer domicile location, marketing effort, customer profession, transmission type and payment method is made. Analysis performed with IBM SPSS v.29 program.The type of Carry passenger vehicle is the choice of many Suzuki customers in Bandung and Suzuki customers mostly come from the people of Bandung and around Bandung who work as entrepreneurs and traders. Suzuki Bandung needs to maintain and improve Canvansing as an effort to acquire customers as can be seen from the analysis of customer segmentation data in this paper